Federalism and Foreign Direct Investment - An Empirical Analysis - Lars P. Feld; Ekkehard A. Köhler; Leonardo Palhuca; Christoph A. Schaltegger (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Previous empirical studies suggest that decentralization, measured by the number of government layers, is associated with less foreign direct investment (FDI). With an improved dataset on tax autonomy of sub-federal government tiers, we present evidence that fiscal decentralization (de facto) does not reduce FDI. If local governments can set their tax rates and bases independently, they attract more FDI. Analyzing 83,458 corporate cross-border acquisitions (CBA), between 148 source and 187 host countries from 1997 to 2014, we also find that takeovers between two countries increase with size, cultural similarities and common borders of two economies. Shared institutions such as membership in a customs union facilitate CBA. These results apply for high-income hosts but not for middle-income countries.
Keywords: G34; H25; H71; 330; fiscal decentralization; cross-border acquisition (CBA); Foreign Direct Investment (FDI); tax autonomy